Ó kdežpak - Wernisch, Ivan, 1942-; Karfík, Vladimír, 1931-; Wernisch, Ivan, 1942- (Praha : Práce, 1991)
Sbírka veršů, jejichž základní tematikou jsou motivy odcizení, promítající se do drobných každodenních událostí.